2022
DOI: 10.1007/s00704-022-03948-2
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally sound alternative cropping systems for rice–wheat systems in North West India

Abstract: Continuous cultivation of Rice-Wheat Cropping System (RWCS) in Indo-Gangetic Plains of India is showing declining factor productivity coupled with many environmental problems. Diversifying the RWCS is one of the environmental friendly options for sustaining food production.Four crop rotations involving maize and sorghum in summer, wheat/ potato/ mustard in winter followed by short duration green gram in late spring were studied to identify the most productive and economic combination from 2017 to 2020. Ranking… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Further, higher benefit cost ratio (> 4) was observed with fruit and fisheries in enterprise mix diversified system. In a different study, Tripathi et al (2021) reported maize-potato-wheat combination best in terms of system productivity with a value of 16.49 t ha −1 . Maize-wheatgreen gram crop sequence was the most profitable by having higher land use efficiency (87.7%) and net returns (1577.1 $ ha −1 ).…”
Section: Miscellaneous Productive Diversification Optionsmentioning
confidence: 98%
“…Further, higher benefit cost ratio (> 4) was observed with fruit and fisheries in enterprise mix diversified system. In a different study, Tripathi et al (2021) reported maize-potato-wheat combination best in terms of system productivity with a value of 16.49 t ha −1 . Maize-wheatgreen gram crop sequence was the most profitable by having higher land use efficiency (87.7%) and net returns (1577.1 $ ha −1 ).…”
Section: Miscellaneous Productive Diversification Optionsmentioning
confidence: 98%
“…Sharma et al (2004);Saroch et al (2005);Triparthi and Singh (2008) reported that diversification of rice cropping sequences particularly with vegetables gave more profit instead of rice cultivation as sole crop. Thus, small and marginal farmers can adopt this sequence to maximise their profit per unit time and space (Tripathi et al, 2022).…”
Section: Economics Of Cropping Sequencementioning
confidence: 99%